Prediction of consolidation from reduced consolidation testing time (continuation) / Md Jalal Bongkik - Bongkik, Md Jalal (1981)
The objective of this project is to study the possibility of reducing the consolidation testing time test. This project is a continuation from last year project. The previous student attempted the prediction or consolidation from reduced consolidation testing time test immediately after the causation of 100% primary consolidation. This was found not satisfactory. Therefore the continuation is made in order to achieve a better result by predicting such test beyond 100% primary consolidation, i.e within the secondary consolidation zone. Prediction of consolidation from such test is entirely based on the S.B. Tan technique. Comparison between the normal and reduced consolidation testing time test had been done to justify the accuracy of the result obtained from reduced test. The variation of result between the two set of test was found within the range of 2% to 7% comparad with previous attempt which was 10% to 20%. Therefore this shows that the prediction made beyond the primary consolidation gives a more accurate result.